1991
DOI: 10.1152/jappl.1991.70.5.2095
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and muscle amino acid and ammonia responses during prolonged exercise in humans

Abstract: Plasma and muscle amino acid (AA) and ammonia (NH3) responses were measured during prolonged submaximal exercise in humans. Increased NH3 production during submaximal exercise has been attributed to the activity of the purine nucleotide cycle, without consideration of any possible contribution from AA. Six men cycled at 75% of maximal O2 uptake until exhaustion on two occasions after 2.5 days of ingestion of a high-carbohydrate or mixed diet. Plasma samples (antecubital vein) and muscle biopsies (vastus latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 0 publications
4
48
0
Order By: Relevance
“…It is also known that oxidation of leucine is elevated during exercise 16) . However, a cycle ergometer exercise to fatigue with a load of 75% V ・ O2max did not alter muscle BCAA levels 39) .…”
Section: C) Bcaasmentioning
confidence: 80%
See 2 more Smart Citations
“…It is also known that oxidation of leucine is elevated during exercise 16) . However, a cycle ergometer exercise to fatigue with a load of 75% V ・ O2max did not alter muscle BCAA levels 39) .…”
Section: C) Bcaasmentioning
confidence: 80%
“…On the other hand, alanine levels increased during exercise, but reverted slightly in response to fatigue 38) . MacLean et al 39) also showed a gradual increase in muscle glutamate levels under a similar workload, and significant increases in alanine levels 45 min after the start of the exercise. Elevated alanine levels reverted to a certain extent at exhaustion (103 ± 8 min).…”
Section: Prolonged Exercise In Humans A) Glutamate Glutamine and Almentioning
confidence: 84%
See 1 more Smart Citation
“…Substantial ammonia and inosinic acid are produced by the deamination of adenosine monophosphate in the skeletal muscle during high-intensity exercise (Stathis et al, 1994). Moreover, the muscle's capacity to produce ATP via oxidative phosphorylation decreases during this process, and muscle fatigue occurs (Sahlin et al, 1990;MacLean et al, 1991). Inhibited homeostasis produced by this ammonia production is recovered by ammonia metabolism in the urea cycle Figure 1 Plasma ornithine, ammonia, urea, lactic acid and glutamate concentrations at times before ingestion, 1 h after ingestion, just after exhaustion and 15 min after exhaustion in both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, because the ammonia production consumes substantial amounts of inosinic acid (Stathis et al, 1994), the ability to produce adenosine triphosphate (ATP) via oxidative phosphorylation in the skeletal muscles decreases. Ultimately, the accumulation of ammonia in skeletal muscle induces muscle fatigue (Sahlin et al, 1990;MacLean et al, 1991) and is linked to a decrease in performance.…”
Section: Introductionmentioning
confidence: 99%